Evaluation of the Role of Pentraxin 3, B-type Natriuretic Peptide and Troponin I in Acute Carbon Monoxide Cardiotoxicity - Alaa Essam Mahmoud; Suzan Mostafa Mahmoud; Mona El KotbMoussa; AyaShawky Khater (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Acute carbon monoxide induced cardiotoxicity is one of the main causes of mortality. It is considered as a poor prognostic factor in patients with carbon monoxide intoxication.Although early diagnosis of cardiac injury is often difficult and might be misdiagnosed.This study aimed to assess the role of Pentraxin 3 and B-type natriuretic peptide in comparison with cardiac Troponin I as early predictors of cardiotoxicity in patients presented with acute CO poisoning. Methods: Thirty patients with acute CO poisoning were recruited from PoisonControl Center, Ain Shams University Hospitals. Serum levels of Cardiac biomarkers (Pentraxin3, BNP and Troponin I) were measured on admission and after 10 hours after exposure. Conclusion: Our results revealed that, B-type natriuretic peptide and Troponin I were more reliable cardiac biomarkers in early prediction of cardiotoxicity in acute CO poisoning patients.While Pentraxin3 had low sensitivity and specificity to predict the cardiotoxicity in acute CO poisoning in comparing with BNP and Troponin I